2021
DOI: 10.48550/arxiv.2106.02716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VEER: Enhancing the Interpretability of Model-based Optimizations

Abstract: Software comes with many configuration options, satisfying varying needs from users. Exploring those options for non-functional requirements can be tedious, time consuming, and even error-prone (if done manually). Worse, many software systems can be tuned to multiple objectives (e.g., faster response time, fewer memory requirements, decreased network traffic, decreased energy consumption, etc.). Learning how to adjust the system among these multiple objectives is complicated due to the trade-off among objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Our study covers seven widely used machine learning models for learning software performance, i.e., Decision Tree (DT) [46] (used by [4,8,25,41]), š‘˜-Nearest Neighbours (š‘˜NN) [21] (used by [35]), Kernel Ridge Regression (KRR) [52] (used by [35]), Linear Regression (LR) [23] (used by [4,8,49]), Neural Network (NN) [53] (used by [20,26]), Random Forest (RF) [30] (used by [45,50]), and Support Vector Regression (SVR) [17] (used by [4,50]), together with five popular real-world software systems from prior work [15,16,41,44], covering a wide spectrum of characteristics and domains. Naturally, the first research question (RQ) we ask is: RQ1: Is it practical to examine all encoding methods for finding the best one under every system?…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study covers seven widely used machine learning models for learning software performance, i.e., Decision Tree (DT) [46] (used by [4,8,25,41]), š‘˜-Nearest Neighbours (š‘˜NN) [21] (used by [35]), Kernel Ridge Regression (KRR) [52] (used by [35]), Linear Regression (LR) [23] (used by [4,8,49]), Neural Network (NN) [53] (used by [20,26]), Random Forest (RF) [30] (used by [45,50]), and Support Vector Regression (SVR) [17] (used by [4,50]), together with five popular real-world software systems from prior work [15,16,41,44], covering a wide spectrum of characteristics and domains. Naturally, the first research question (RQ) we ask is: RQ1: Is it practical to examine all encoding methods for finding the best one under every system?…”
Section: Research Questionsmentioning
confidence: 99%
“…We shortlisted systems and their data from recent studies on software configuration tuning and modeling [41,44], from which we identified five systems and their environment according to the above criteria, as shown in Table 2. The five systems contain different percentages of categorical/binary and numeric configuration options while covering five distinct domains.…”
Section: System and Data Selectionmentioning
confidence: 99%